Peran public relations di perguruan tinggi: teknis atau manajerial? - Intan Primadini; Angelia Heriyanto; Naomi Tehillah; Kadek Tri Anggraeni S. C. P; Chininta Rizka Angelia (Jurnal Komunikasi Profesional, 2022)
Educational institutions, especially higher education, have long been aware of the role of Public Relations practitioners to perform structured communication activities. However, there are still many university leaders, even public relations practitioners themselves who do not understand their role in helping organizations achieve their goals. In general, the role of Public Relations practitioners is divided into two, namely technical and managerial. This study aims to analyze the role of Public Relations practitioners in higher education institution, especially Universitas Indonesia, using The Five-Factor Dimension Model. This is a descriptive qualitative research and the data is obtained through in-depth interviews with six participants. The results of the study show that Public Relations practitioners at Universitas Indonesia has ideally implemented both technical and managerial roles. However, their role is still dominated by technical role rather than managerial role.